2001
DOI: 10.1097/00006123-200103000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cyclooxygenase-2 in Rabbit Basilar Artery Endothelial Cells after Subarachnoid Hemorrhage

Abstract: After SAH, endothelial COX-1 immunoreactivity does not change, whereas overexpression of COX-2 occurs at 3 days. This induction does not seem linked to TNFalpha production, nor is it responsible for early raised levels of PGE2 and PGI2 in the CSF. We suggest that the role of induced COX-2 may be to modify gene expression and hence alter the properties of the vessel wall after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…We observed that hemolysate induced the production of several inflammatory mediators as well as the activation of NF-кB in vitro . We also confirmed that COX-2 and iNOS were produced in the rat femoral artery model, similar to the results with experimental SAH models previously described [19,20]. Our in vivo and in vitro studies clearly showed trehalose suppressed these inflammatory responses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that hemolysate induced the production of several inflammatory mediators as well as the activation of NF-кB in vitro . We also confirmed that COX-2 and iNOS were produced in the rat femoral artery model, similar to the results with experimental SAH models previously described [19,20]. Our in vivo and in vitro studies clearly showed trehalose suppressed these inflammatory responses.…”
Section: Discussionsupporting
confidence: 91%
“…These cells play important roles in inflammation after SAH [19-22]. The hemolysate (see below) was used for in vitro studies on blood-induced inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that many of the inflammation‐related genes are upregulated in vasospastic arteries relative to control 24 . Upregulation of cyclo‐oxygenase‐2 25 and 5‐LOX 18 in rabbit and canine basilar artery after SAH has also been reported. Furthermore, it was found that the 5‐LOX inhibitors are effective in preventing or attenuating cerebral vasospasm in rabbit and canine models of SAH 26,27 .…”
Section: Discussionmentioning
confidence: 92%
“…41, 44 Celecoxib is likely to provide neuroprotective and anti-inflammatory effects via to its clinically utilized COX-2 inhibitory activity. 45-47 …”
Section: Discussionmentioning
confidence: 99%